SIKAP PETANI TERHADAP PENGGUNAAN STIMULAN PADA TANAMAN MENGHASILKAN KARET DI KECAMATAN RIMBO BUJANG KABUPATEN TEBO - Yoga Hardanto, Flangga; Lubis, Arsyad; Sardi, Idris (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2021)
This research aims to measure the farmer attitude on using stimulant on the rubber plant at Rimbo Bujang district, Tebo Regency and also to find the relationship between their attitude and the result that they got. The research started from early Marc to April 2018. Things that observed here consist of cognitive, affective, and conative. Harry King said that to calculat various sample fro 5 to 15 % so we have to use Slovin method and the resercher stated that the 15% of false from 533 so there was only 76 respondents. The data analysis used in this research are descriptive and cuantitative method by chi-square statistict on 2x2 contigency tabel with 5% bias. The result of data analysis showed that the farmer attitude on using stimulat for their rubber plants has proven positively and there's also have significant relationship between the using stimulant and their attitude by result thit = 8,06 > ttab = 1,66571 so reject H0 receive by H1. It means that there's a significant relationship between farmer's attitude on using stimulant on the rubber plants in Rimbo Bujang district Tebo Regency in real.